AUTOMATIC HONEY FILTER EQUIPPED WITH JACK SCREW SYSTEM - Adhitya Wira Dharma; Achmad Rianto; Maulana Ridhwan; Andriyanti Achsan; Asrul Ludin; Agung Prijo Budijono (AIBPM Publisher, 2018)
The purpose The purpose of this study is to provide solutions to existing problems in SMEs Honey in the area of Malang which is still using the traditional way in the process of filtering honey that has been applied. Method The method used is to utilize the Jack Screw system as an alternative to pressing and filtering honey. In addition to this tool is also equipped with an ECU as a control system to regulate the working mechanisms that exist in the tool. ResultThe expected result is to improve the quality of honey filtering so as to increase the productivity of SME Honey up to 400%. Early production of 3kg (6 hours working) can increase to 25kg of honey filtered every day. The findingThe findings of this study is the use of Screw Jack as an effort to improve the quality of screening so that the productivity and quality of honey in SMEs can be increased. Keywords :Honey, FiltersHoney, ScrewJack Systems, ECU